UNDERSTANDING THE MEANING OF HUMAN TOUCH MANAGEMENT - Kim, A Young; Wisesa, Anggara (Journal of Business and Management, 2017)
Abstract. According to the Oxford Dictionaries, a leader is the person who leads or commands a group, organization, or country. A leader needs people [followers] who want to follow and listen to him. Being in charge of a group of people is not just about leading and commanding but it means inspiring people and encouraging them to become better ones. When a leader does those things, he could finally be called as a good leader. The researcher found a CEO who can be stated that he is a good leader based on that definition. The CEO of XXX Company was the one the researcher found. Although he had different cultural background he has been doing his job well and known for his leadership called Human Touch Management. Even if it was one of the factors that lead him to be successful in his career and helped the company to grow, there was not enough information about Human Touch Management. Therefore the researcher decided to study about it and get more information about HTM. In this research, the researcher discussed about what Human Touch Management (HTM) means and what leadership style it belongs to. In order to define what HTM is, the researcher had visited the XXX Company to observe, meet the CEO who created it, and did in depth interview. The researcher could define that Human Touch Management is the leadership style which thinks employees as the most important asset of company and it is human-oriented leadership. It requires leaders to study about human including psychological, physical, and mental factors. By studying about human, the leader can understand why and how human being behaves, thinks, and says. Then, it helps him to know how to develop himself and understand his employees better. Based on those outcomes, the researcher concludes that Human Touch Management can be stated it belongs to Principle-Centered Leadership and Servant Leadership. Â Key words: Foreign Leader, Human Touch Management, Leadership, Leadership styles, and Shoe Industry.